2020
DOI: 10.1002/2211-5463.12878
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating natural antibodies against CD25, MUC1, and VEGFR1 for early diagnosis of non‐small cell lung cancer

Abstract: We previously demonstrated that a deficiency of natural antibodies against CD25, Mucin 1 (MUC1), and vascular endothelial growth factor receptor 1 (VEGFR1) could contribute to high risk of non-small cell lung cancer (NSCLC). This study was designed to investigate whether natural IgG antibodies against POU domain class 5 transcription factor 1 (POU5F1), tumor necrosis factor-a (TNF-a), and the combination of CD25, VEGFR1, and MUC1 could play an anti-tumorigenic role against developing NSCLC. An ELISA was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Interestingly, a deficiency of natural antibodies against CD25, Mucin 1 (MUC1), and vascular endothelial growth factor receptor 1 (VEGFR1) has been proposed to contribute to high risk of NSCLC. In fact, levels of auto-antibodies against these antigens have been found to be systematically lower in NSCLC patients than control subjects [ 86 ]. Impressively, an optimized panel with four biomarkers (CEA, CA125, Annexin A1-Ab, and Alpha enolase-Ab) was established presenting an area under the receiver operator characteristic curve of 0.897, a sensitivity of 86.5%, a specificity of 82.3%, a positive predictive value (PPV) of 88.3%, a negative predictive value (NPV) of 79.7%, and a diagnostic accuracy of 84.8% for the training group [ 87 ].…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…Interestingly, a deficiency of natural antibodies against CD25, Mucin 1 (MUC1), and vascular endothelial growth factor receptor 1 (VEGFR1) has been proposed to contribute to high risk of NSCLC. In fact, levels of auto-antibodies against these antigens have been found to be systematically lower in NSCLC patients than control subjects [ 86 ]. Impressively, an optimized panel with four biomarkers (CEA, CA125, Annexin A1-Ab, and Alpha enolase-Ab) was established presenting an area under the receiver operator characteristic curve of 0.897, a sensitivity of 86.5%, a specificity of 82.3%, a positive predictive value (PPV) of 88.3%, a negative predictive value (NPV) of 79.7%, and a diagnostic accuracy of 84.8% for the training group [ 87 ].…”
Section: Cancer Auto-antibodiesmentioning
confidence: 99%
“…Natural autoantibodies are an important component contributing to the anti‐tumor system in the body and have shown a decrease in circulating levels among patients with early stage cancer (Liu et al, 2020; Zhao et al, 2018). It has been supposed that natural autoantibodies may be useful anti‐cancer agents for postoperative therapies to prevent the recurrence of human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that the abnormal expression of MUC1 was correlated with the poor prognosis of patients with lung adenocarcinoma ( 23 ). Results indicate the potential utility of MUC1 as a clinical diagnostic marker and therapeutic target for lung adenocarcinoma through the contributing role in pathological features, such as development and invasive metastasis ( 24 ).…”
Section: Muc1 Expression In Different Tumours and Its Clinical Signif...mentioning
confidence: 99%